Priority research topics to improve streamflow data availability in data-scarce countries: the case for Ethiopia - Taye, Meron Teferi; Zimale, Fasikaw A.; Woldesenbet, T. A.; Kebede, M. G.; Amare, S. D.; Tegegne, G.; Mekonnen, K.; Haile, Alemseged Tamiru (MDPI, 2023)
Lack of consistent streamflow data has been an increasing challenge reported by many studies in developing countries. This study aims to understand the current challenges in streamflow monitoring in Ethiopia to prioritize research topics that can support sustained streamflow monitoring in the country and elsewhere. A workshop-based expert consultation, followed by a systematic literature review, was conducted to build a collective understanding of the challenges and opportunities of streamflow monitoring in Ethiopia. The experts’ consultation identified the top ten research priorities to improve streamflow monitoring through research, education, remote sensing applications, and institutions. The experts’ views were supported by a systematic review of more than 300 published articles. The review indicated scientific investigation in Ethiopian basins was constrained by streamflow data gaps to provide recent and relevant hydrological insights. However, there is inadequate research that seeks solutions, while some researchers use experimental methods to generate recent streamflow data, which is an expensive approach. Articles that attempted to fill data gaps make up less than 20% of the reviewed articles. This study identified research priorities that can benefit streamflow data providers and the research community in alleviating many of the challenges associated with streamflow monitoring in countries such as Ethiopia.